Structuring Edible Oils With Fumed Silica Particles - Whitby, Catherine P. (Frontiers in Sustainable Food Systems, 2020)
Organogels are often made from solutions of proteins, polymers or fatty acids in oil. The macromolecular species crystallize, or assemble, into mesh structures that inhibit oil flow. This review focuses on using fumed silica nanoparticles as an alternative structuring agent. Fumed silica particles have a unique, branched morphology that means the particles aggregate into three-dimensional, interconnected networks. Two key aspects for formulating edible oleogels are addressed. Advances in our understanding of fumed silica particle aggregation in oil that point toward strategies for tuning the rheological properties of oleogels are examined. Secondly, the factors likely to affect the lipolysis of oils structured used fumed silica particles, and hence the bioavailability of ingredients loaded into the gels, are discussed. The next challenge for these promising materials is to target suitable applications for their use as fat replacement in foods.